Outcome of Mini-Percutaneous Nephrolithotomy in Patients Under the Age of 18: An Experience With 112 Cases - Hosseini, Mohammad Mehdi; Irani, Dariush; Altofeyli, Ala'a; Eslahi, Ali; Basiratnia, Mitra; Haghpanah, Abdolreza; Adib, Ali; Ahmed, Faisal (Frontiers in Surgery, 2021)
Purpose: Renal calculi are becoming more common among children. Although, extracorporeal shock wave lithotripsy (ESWL) is the first choice in this age group, minimal invasive surgeries, such as percutaneous nephrolithotomy (PCNL), are indicated for some patients. Recently, PCNL devices have become smaller in size with acceptable efficacy and lower complications. We evaluated the outcomes and complications of mini-PCNL (MPCNL) surgery in our referral training centers. Materials and Methods: Between September 2012 and January 2020, a total of 112 children under the age of 18, who had shown failure of ESWL, and/or their parents refused to do it, underwent MPCNL (15 Fr). The patients' profiles were reviewed for data collection including preoperative and stone data, operation information, and postoperative complications. Results: Of 112 patients, 69 were boys, and 43 were girls. Their mean age was 8.6 years (14 months to 18 years). Mean stone size was 20 mm (14–34 mm). Seventy-four cases had renal pelvic stone, 22 had pelvis and lower pole, and 16 had staghorn. The mean operation time was 65 min (35–100 min), and mean radiation time was 0.6 min (0.2–1.4 min). Low-grade fever was detected in 14 patients (12.5%). Four patients needed blood transfusion and two had increased creatinine, which improved with conservative management. One patient developed urosepsis that resolved with antibiotic therapy. None of the patients had kidney perforation or other organ injury or death. Early stone-free rate (SFR) after operation was 90.2% (101 patients). Six patients had residual fragment <5 mm, which passed spontaneously in 2 weeks after operation (total SFR 95.3%). Three patients underwent second-look nephroscopy, and ureteroscopy was done for two patients due to migrated stone fragments to the distal ureter. Conclusion: MPCNL is recommended as a safe alternative option for treatment of the nephrolithiasis in children with good outcome and acceptable complications.